Political Capital, Social Networks, and Electoral Leadership: Explaining Non-Party Candidate Success in Jakarta’s Local Elections - Tjahjadi, Syony; Labolo, Muhadam; Nurdin, Nurliah; Megandaru, Megandaru (Ilomata International Journal of Management, 2026)
Since the introduction of direct regional head elections in Jakarta in 2007, no incumbent governor has successfully secured a second term. This pattern indicates a unique electoral dynamic where candidates who are not strongly rooted in political party structures can compete effectively. This study examines the factors behind the victory of a non-party candidate in the 2017 Jakarta gubernatorial election and discusses its implications for political party recruitment. Using a qualitative case study approach, data were collected through in-depth interviews, observation, and document analysis involving 20 informants, including political elites, campaign team members, academics, and community leaders. The analysis applies Pierre Bourdieu’s theory of capital to understand how political, social, and economic capital interact in electoral competition. The findings show that electoral success is no longer determined solely by party machinery but by the strategic combination of different forms of capital. Among these, social capital such as public trust, community networks, and shared identity play a particularly important role in mobilizing voter support. The study concludes that success in local elections depends on the dynamic interaction between political, social, and economic capital. Based on these findings, the study proposes a preliminary framework for political party recruitment that emphasizes candidate performance and the development of social capital as key elements for strengthening democratic leadership.